Field oriented controlled permanent magnet synchronous motor drive for an electric vehicle - Chau Si Thien Dong; Hoang Huy Le; Hau Huu Vo (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
The paper describes field oriented control strategy with space vector pulse width modulation technique of permanent magnet synchronous motor drive system for an electric vehicle. At first, mathematical models of the motor and the drive system for electric vehicle are presented. In order to obtain high performance drive and maximum motor torque, field oriented control strategy and space vector pulse width modulation technique method are applied to drive system in next section. Speed controller design utilizing the popular zero-pole elimination approach causes large integral constant time in case ofÂ  small rotational damping constant. The desired-transient-response-based approach is employed to overcome the problem. Performance indices include overshoot, undershoot, steady-state speed error, and total harmonic distortion of stator current, are employed to assess the drive systems with two speed controller design methods. Theoretical assumptions are confirmed via simulations and criteria in MATLAB/Simulink environment.